PENGARUH PENGUASAAN TRIGONOMETRI TERHADAP HASIL BELAJAR MATEMATIKA TEKNIK PENGINTEGRALAN DI KELAS XII TEKNIK KOMPUTER JARINGAN (TKJ) SMK NEGERI 1 PADANGSIDIMPUAN - Sukriadi Hasibuan (Institut Pendidikan Tapanuli Selatan, 2018)
Abstract This study aims to look at the influence of mastery of trigonometry mathematics learning outcomes in class XII Integration techniques of computer engineering network SMK Negeri 1 Padangsidimpuan. Total population of 124 people. random sampling techniques are drawn as many as 32 ​​people. Data were collected in 2 ways analyzed first descriptive analysis to see the general picture of the two variables. while the second is inferential statistical analysis using t-test. Mastery of trigonometry has an average value of 67.71, so that in the category of